2014
DOI: 10.1017/jfm.2014.319
|View full text |Cite
|
Sign up to set email alerts
|

Self-propelled jumping upon drop coalescence on Leidenfrost surfaces

Abstract: Self-propelled jumping upon drop coalescence has been observed on a variety of textured superhydrophobic surfaces, where the jumping motion follows the capillary–inertial velocity scaling as long as the drop radius is above a threshold. In this paper, we report an experimental study of the self-propelled jumping on a Leidenfrost surface, where the heated substrate gives rise to a vapour layer on which liquid drops float. For the coalescence of identical water drops, we have tested initial drop radii ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(126 citation statements)
references
References 21 publications
5
121
0
Order By: Relevance
“…Thea nisotropic adhesion of the MATS surface also has ap rofound influence on the coalescence-induced leaping behavior of condensed water microdroplets.T ypical side-view snapshots of the guided self-propelled leaping behavior of coalesced water microdroplets on the MATS surface are shown in Figure 2a (top-view images are displayed in the Supporting Information, Figure S4), and are compared sideby-side with typical snapshots taken on an isotropic nanostructured superhydrophobic surface (NASS surface). Consistent with previous reports, [12] the spontaneous jumping direction on the NASS surface was mostly vertical, with as tatistically random nature.I ns harp contrast, the leaping direction on the MATS surface demonstrated ac lear bias in the positive direction. Ap ositive direction is defined by the 2D statistical distribution of the angles of leaping events (Supporting Information, Figure S3).…”
supporting
confidence: 92%
“…Thea nisotropic adhesion of the MATS surface also has ap rofound influence on the coalescence-induced leaping behavior of condensed water microdroplets.T ypical side-view snapshots of the guided self-propelled leaping behavior of coalesced water microdroplets on the MATS surface are shown in Figure 2a (top-view images are displayed in the Supporting Information, Figure S4), and are compared sideby-side with typical snapshots taken on an isotropic nanostructured superhydrophobic surface (NASS surface). Consistent with previous reports, [12] the spontaneous jumping direction on the NASS surface was mostly vertical, with as tatistically random nature.I ns harp contrast, the leaping direction on the MATS surface demonstrated ac lear bias in the positive direction. Ap ositive direction is defined by the 2D statistical distribution of the angles of leaping events (Supporting Information, Figure S3).…”
supporting
confidence: 92%
“…Several authors have reported that, on superhydrophobic or Leidenfrost surfaces, the escape velocity is proportional to the capillary velocity v cap =  γ ow ρ w R 0 , with a sharp viscous cutoff for small radii. 4,19 Using the non-dimensional formulation of the equations of motion, we can readily simulate droplets of different radii R using the settings of the two jumps examined in Figure 4 smaller drops, we expect the dissipation to become more relevant, to the point that jumps will no longer occur for droplets smaller than a critical radius. In Figure 7, we plot the normalized jump height versus the droplet radius R. We observe that, for R > 0.3 mm, the normalized height slowly decreases with increasing drop size R, as the Bond number of the system increases.…”
Section: Fig 5 (A) Energetic Analysis Of the Jump Frommentioning
confidence: 99%
“…Liu and colleagues have taken a significant step towards a systematic analysis of droplet recoil and leap by studying head-on collision of microdroplets on Leidenfrost surfaces. 18,19 In this study, we use electrowetting to induce the controlled deformation and subsequent ejection of water droplets on a solid substrate immersed in silicone oil. By applying a voltage between the conductive droplet and substrate, we significantly reduce the contact angle of the system, 20 causing the droplet to spread.…”
Section: Introductionmentioning
confidence: 99%
“…The jumping velocity is measured from the trajectory of coalesced droplet which is recorded using the mass center based on video images. 46 The dimensionless jumping velocity is given by v à 5v= ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi ffi r lv = qR 0 ð Þ p . The jumping velocity is approximately constant with v à $ 0:2 for small initial droplet radii (R 0 <0.70 mm), which is consistent with the reported velocity.…”
Section: Jumping Velocity Of the Coalesced Dropletmentioning
confidence: 99%